HUBUNGAN DEIKSIS PERSONA DAN DEIKSIS SOSIAL DALAM FILM《悲伤逆流成河》Bēishāng nìliú chénghé CRY ME A SAD RIVER KARYA LUO LUO - Utami Rahmawati; Muhammad Farhan Masrur (Universitas Negeri Surabaya, 2022)
Besides being used for exchanging information, language is also used by humans to refer to one thing in a context. Without context, the interlocutor will find difficulties to understand the meaning of the designation expressed by the speaker. In pragmatics, the expression of designation is called deixis. There are four types of deixis, personal diexis, social deixis, time deixis, and place deixis. Personal deixis and social deixis are types of deixis that have a close relationship. This research aims to discuss the relationship between personal deixis and social deixis in the film Cry Me a Sad River《悲伤逆流成河》Bēishāng Nìliú Chénghé by Luo Luo. This research is qualitative research with the data in the form of speech transcripts containing personal deixis and social deixis. The method used is descriptive method. This study used the simak bebas libat cakap technique and note-taking techniques. The following results were obtained: (1) the speech transcripts contained 192 data of personal deixis and 21 data of social deixis. (2) There is a connection between personal deixis and social deixis, namely aspects of social deixis influence the speaker's choice of personal deixis. Key Words: Deixis, Relationship, Personal Diexis, Social Deixis, Cry Me a Sad River